2009
DOI: 10.1002/lapl.200810092
|View full text |Cite
|
Sign up to set email alerts
|

In vivoRaman spectroscopy detects increased epidermal antioxidative potential with topically applied carotenoids

Abstract: Abstract:In the present study, the distribution of the carotenoids as a marker for the complete antioxidative potential in human skin was investigated before and after the topical application of carotenoids by in vivo Raman spectroscopy with an excitation wavelength of 785 nm. The carotenoid profile was assessed after a short term topical application in 4 healthy volunteers. In the untreated skin, the highest concentration of natural carotenoids was detected in different layers of the stratum corneum (SC) clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
102
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 22 publications
(28 reference statements)
4
102
0
2
Order By: Relevance
“…It is known that carotenoids and other lipophilic compounds such as vitamin E are delivered to the skin by blood [2,7] and sebaceous glands [47]. The transport of carotenoids via the sweat glands has been discussed by Lademann et al [48]. Hence, the uptake of vitamin C and carotenoids follows different pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that carotenoids and other lipophilic compounds such as vitamin E are delivered to the skin by blood [2,7] and sebaceous glands [47]. The transport of carotenoids via the sweat glands has been discussed by Lademann et al [48]. Hence, the uptake of vitamin C and carotenoids follows different pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Confocal Raman spectroscopy has already been applied for analysis of skin hydration status [8], the effect of penetration enhancers [9] and the epidermal antioxidative potential [10,11] of skin. In vitro follow-up studies of metronidazole [12] and phospholipids [13] indicated the potential of confocal Raman microscopy for penetration experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing use of CRM to establish skin penetration profiles has led to an increasing variety of microscope configurations and sample preparation methods used therein (table 1) [3,4,13,14,15,16,17,18,19,20,21,22,23,24]. …”
Section: Introductionmentioning
confidence: 99%